SLUG‐related partial epithelial‐to‐mesenchymal transition is a transcriptomic prognosticator of head and neck cancer survival. Issue 2 (21st August 2021) - Schinke, Henrik; Pan, Min; Akyol, Merve; Zhou, Jiefu; Shi, Enxian; Kranz, Gisela; Libl, Darko; Quadt, Tanja; Simon, Florian; Canis, Martin; Baumeister, Philipp; Gires, Olivier
Abstract : Partial epithelial‐to‐mesenchymal transition (pEMT) contributes to cellular heterogeneity that is associated with nodal metastases and unfavorable clinical parameters in head and neck squamous cell carcinomas (HNSCCs). We developed a single‐cell RNA sequencing signature‐based pEMT quantification through cell type‐dependent deconvolution of bulk RNA sequencing and microarray data combined with single‐sample scoring of molecular phenotypes (Singscoring). Clinical pEMT‐Singscores served as molecular classifiers in multivariable Cox proportional hazard models and high scores prognosticated poor overall survival and reduced response to irradiation as independent parameters in large HNSCC cohorts [The Cancer Genome Atlas (TCGA), MD Anderson Cancer Centre (MDACC), Fred Hutchinson Cancer Research Center (FHCRC)]. Differentially expressed genes confirmed enhanced cell motility and reduced oxidative phosphorylation and epithelial differentiation in pEMT high patients. In patients and cell lines, the EMT transcription factor SLUG correlated most strongly with pEMT‐Singscores and promoted pEMT, enhanced invasion, and resistance to irradiation in vitro . SLUG protein levels in HNSCC predicted disease‐free survival, and its peripheral expression at the interphase to the tumor microenvironment was significantly increased in relapsing patients. Hence, pEMT‐Singscores represent a novel risk predictor for HNSCC stratification regarding clinical outcome and therapy response that is partly controlled by SLUG. Abstract : In a combinatorial approach, a single‐cell RNA sequencing‐derived partial epithelial‐to‐mesenchymal transition (pEMT) gene signature was transferred to bulk sequencing data from large head and neck squamous cell carcinoma cohorts using single‐sample scoring (Singscoring). Patient‐specific pEMT‐SingScores prognosticated patient overall survival and reduced response to irradiation as an independent parameter. pEMT‐SingScores correlated with the expression of the transcription factor Slug, which induced characteristics of pEMT and correlated with reduced disease‐free survival.